Avaliação de política ambiental e sustentabilidade: Estudo de caso do município de Santo André - SP - Cezare, Juliana Pellegrini [UNESP]; Malheiros, Tadeu Fabricio; Philippi Jr., Arlindo (FapUNIFESP (SciELO), 2007)
The management of the São Paulo Metropolitan Area has as one of the challenges to bring a sustainable solution for land use in watershed protection areas, aiming at regional water resources protection. This paper has the objective to contribute to the discussion about Sustainable Development Strategy Assessment, from an analisys with focus at the environmental policies of the Santo André City - SP Brazil, in the context of water resources protection. For this, the proposal is to verify, based on the Bellagio Principles, the use of systemic approach, transparency, participatory process and social engagement in its policy formulation and implementation process. It was observed coherence within the policies, programmes and actions analysed, nevertheless, gaps were identified, which, within a strategic approach, means weakness for the construction of the local sustainability, as the lack of a consolidated sustainability indicators system.
Environmental policy assessment and sustainability: Case study of Santo André City - SP - Brazil
Keywords: Strategic assessment; Sustainability; Water resources